A research agenda for professional learning communities: moving forward. Issue 1 (1st January 2017) - Hairon, Salleh; Goh, Jonathan Wee Pin; Chua, Catherine Siew Kheng; Wang, Li-yi
Abstract : Professional learning communities (PLCs) as a means of raising the teaching profession are becoming more attractive in education systems seeking to improve school improvement processes and outcomes. The main intention is to increase the individual and collective capacity of teachers so as to support school-wide capacity for teaching and learning. Although international research on PLCs is relatively extensive, covering about three decades, there are still gaps in its research base; specifically on the concept of community and the effects of PLCs. In this article, we propose a research agenda for PLC research that will afford substantive theorization on PLCs which will need to be drawn from robust empirical evidence. In the proposed research agenda for PLCs, we first argue that a PLC is a multi-dimensional construct comprising three inter-dependent dimensions of 'community', 'learning' and 'professional'. This precedential task is necessary before investigations on effects or impact (direct or indirect) of PLCs can be meaningfully and reliably carried out. We then propose a research framework for PLCs constituting three aspects: construct of PLCs; conditions–contexts of PLCs; and causalities of PLCs. Finally, we propose six aspects pertaining to methodological rigor to support PLC research.